ASIMILASI LONTARA PANGADERENG DAN SYARI'AT ISLAM: Pola Perilaku Masyarakat Bugis-Wajo - Nawawi, Nurnanigsih (IAIN Ponorogo, 2015)
Abstract: This study is aimed at showing the concepts of cultural values of Bugis society in Wajo, comprising of the values such as honesty, expertness, truth, mercy, and business summarized in the system of